THE IMPACT OF UNEMPLOYMENT ON SUBSTANCE ABUSE: A STUDY ON THE YOUTH OF KASHMIR - Mohd Arif Naikoo; Aamer Nabi Ganaie (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
This study examines the relationship between unemployment and substance abuse among the youth of Kashmir. Given the region's complex socio-political environment, high unemployment rates, and increasing reports of substance abuse, it is crucial to understand the underlying dynamics. Through a mixed-methods approach, this research aims to provide a comprehensive analysis of how unemployment contributes to substance abuse among Kashmiri youth and to suggest potential